Asylum Adjudication, Mental Health and Credibility Evaluation*. (September 2013) - Hunter, Jill; Pearson, Linda; Roque, Mehera San; Steel, Zac
This article examines the central role that credibility assessment plays in refugee determinations. It draws on the authors' own empirical study, Tales of the Unexpected, to display the complex ways in which applicants' poor mental health can affect their capacity to present a 'coherent and plausible' account of their experiences. The authors then explore the significant issues arising from the tendency revealed in the Tales study for decision makers to dismiss expert opinions expressed in reports tendered by applicants from psychologists specialising in cross-cultural mental health assessment. For example, consider the decision maker who observed that [The] psychologist reported that the Applicant was suffering from post-traumatic stress disorder and depression and that this psychological state was likely to affect his ability to answer questions at an RRT hearing …. [Nevertheless] [Mr S] did not display any difficulty in understanding or answering questions. … He [appeared] alert, engaged, and is clearly an intelligent man. I do not accept that he had any difficulty in understanding proceedings or answering questions. 5